Management of intellectual property uncertainty in a remanufacturing strategy for automotive energy storage systems - Ian Hartwell; James Marco (Journal of Remanufacturing, 2016)
Legislative requirements are motivating vehicle manufacturers to produce innovative electric vehicle (EV), hybrid electric vehicle (HEV) and plug-in hybrid electric vehicle (PHEV) concepts. End-of-Life (EOL) for the vehicle's battery is often taken to be the battery having 80% retained capacity. Even at this lower threshold, there is still considerable inherent value embedded within the battery system. The extraction of raw materials through recycling and the use of the battery in second life applications are widely documented. In contrast, there has been relatively little research published that investigates the options and requirements for remanufacturing the vehicle's battery system as one means of improving the efficiency of the overall production process. This paper addresses two of the barriers, often cited, that inhibit organizations from adopting a remanufacturing strategy-ambiguity regarding the meaning of remanufacturing and uncertainty in how to manage intellectual property (IP). Based on a critical review of UK law and legal decisions pertaining to remanufacturing, the authors propose a revised set of definitions for circular economy activities, exploiting the terms: warranty and design-life to provide a clear differentiation for remanufacturing. The authors also propose a new framework for managing IP uncertainty. The model may be employed by both original equipment manufacturers (OEMs) to protect their innovations and remanufacturing activities and by independent organizations seeking to remanufacture OEM products.
Keywords: 650; Remanufacturing; Intellectual property; Circular economy; Transport; Electric vehicles; Energy storage